Q. 10 E3.7( 3 Votes )

<span lang="EN-US

Answer :


(x+1)(x+2) – (x–1)(x–3) = 4 × 3 – 1 × (–1)


(x2 + 2x + x + 2) – (x2 – 3x – x + 3) = 12 + 1


–2x –1= 13


–2x = 14


x = –7


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers